PENDUGAAN BIOMASSA ATAS PERMUKAAN DI KPHP UNIT X TEBO TIMUR: Above Ground Biomass Estimation at KPHP Unit X Tebo Timur - Agus Kurniawan Mastur; Eva Achmad; Bremi Renata Simbolon (Fakultas Kehutanan Universitas Jambi, 2021)
Plant biomass is a carbon storage. The amount of biomass depends on the vegetation. This study aimed to analyze and predicted the above ground biomass stock in KPHP Unit X Tebo Timur. Regression analysis was used by correlating the biomass value from field measurement and the NDVI value from Landsat 8 imagery. Some of the regression equations tested were: linear, exponential, quadratic and rank. The best regression equation is used to estimate the biomass stock in KPHP Unit X Tebo Timur. The best model used to estimate above ground biomass stocks based on the NDVI value in East Tebo KPHP is quadratic with the equation Y = 574.05 ((NDVI) 2) - 17.24 (R2 = 85.5%). The analysis results showed that the above ground biomass stock in KPHP Unit X Tebo Timur was 9,695,091.39 tons.